Self-Adaptive Upper Limb Prosthetic Socket - Polizzotto, Maria Grazia; Zaidi, Ahmed Zohaib; Paterno, Linda; Menciassi, Arianna (Proceedings of the ... IEEE/RAS-EMBS International Conference on Biomedical Robotics and Biomechatronics, 2024)
This paper proposes a self-adaptive trans-humeral prosthetic socket employing soft actuators to address issues of discomfort and pain caused by changes in residual limb volume over time. Specifically, the proposed solution integrates McKibben actuators, a sensorized prosthetic liner, and a wearable control unit to ensure proper prosthesis fitting. The system can be commanded by the user through a mobile app. Three sizes of McKibben actuators with 3, 5, and 8 mm diameters (small, medium, and large), and 8 cm length, were manufactured and tested. Maximum strain of 19.44 ± 0.7{%} , I 24.25 ± 0.71%.\ 25.64± 0.5{%} . and maximum output force of 7.04 ± 0.34 N, 12.29 ± 0.19 N, 19.28 ± 0.97 N were obtained at 1 bar inlet pressure for small, medium and large actuators, respectively. Based on these results, eight large actuators were used in the final system, which was preliminary validated on a physical simulator and a healthy subject, demonstrating effective adaptation to volume changes and contact pressure feedback control. This smart socket is a promising solution for improving comfort and usability in upper limb prostheses.